The impact of war in Ukraine on the inbound tourism in Lithuania: replication of studies - Variakojienë, Jolita; Achonen, Irena; Vaitkevičiűtë, Justina (Turystyka i Rozwój Regionalny, 2023)
The objective of this paper is to examine the planning international arrivals toLithuania in 2023 and to determine the impact of the war on Lithuanian incoming tourisma year on from the Russian invasion of Ukraine. The hypotheses that war in Ukraine hasa long-lasting effect decreasing the number of tourist arrivals in the region were tested usinga quantitative research method. To do so, the data was collected through an online survey,targeting Lithuanian inbound tour operators providing ground services for internationaltourists in Lithuania. The timing of the survey (2023, April) provided opportunity to examinethe effect of war in Ukraine on inbound tourism. The findings indicate that tourists feel fearabout the war and cancel their travel orders. Comparing two surveys, in 2023 tour operatorsreceive fewer cancellations and more bookings than 2022. Tourists from Germany, the UnitedStates of America, France, Italy and the United Kingdom have cancelled the most bookings inboth years. The main reasons for the decrease in tourist flows are the unsafe situation and thefear of traveling due to the war.